2016
DOI: 10.7150/ijbs.12852
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic-therapy Activates Immune Response by disrupting Immunity Homeostasis of Tumor Cells, which Generates Vaccine for Cancer Therapy

Abstract: Photodynamic therapy (PDT), a regulatory approved cancer treatment, is reported to be capable of causing immunogenic apoptosis. The current data reveal PDT can cause the dysregulation of “eat me” and “don't eat me” signal by generating reactive oxygen species (ROS) -mediated endoplasmic reticulum (ER) stress. This dysregulation probably contribute to the increased uptake of PDT-killed Lewis lung carcinoma (LLC) cells by homologous dendritic cells (DCs), accompanied by phenotypic maturation (CD80high, CD86high,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 35 publications
1
63
0
1
Order By: Relevance
“…This exposure of immunogenic molecules after NB-PDT was the next event explored in this study. Conventional PDT is described to induce exposure of HSP70, among other chaperones, on the membrane of tumor cells [28][29][30][31]. Membrane exposure of HSP70 was indeed observed on A431 and scc-U8 cells treated with mild NB-PDT, although it was more evident on the high EGFR-expressing cells at the early timepoint studied (Figure 2a,b).…”
Section: Discussionmentioning
confidence: 99%
“…This exposure of immunogenic molecules after NB-PDT was the next event explored in this study. Conventional PDT is described to induce exposure of HSP70, among other chaperones, on the membrane of tumor cells [28][29][30][31]. Membrane exposure of HSP70 was indeed observed on A431 and scc-U8 cells treated with mild NB-PDT, although it was more evident on the high EGFR-expressing cells at the early timepoint studied (Figure 2a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Mice which were systemically depleted of DCs showed 90% of disease recurrence compared to only 20% in mice which received PDT treatment only [36]. Furthermore, other reports support the involvement of DCs in the response to PDT as evidenced by enhanced maturation and activation as well as increased secretion of proinflammatory cytokines after treatment [37,38,39,40]. …”
Section: Pdt and Innate Immunitymentioning
confidence: 99%
“…Zheng et al found a decrease of Treg induction in vitro and in vivo in response to stimulation/treatment with DC which had been pulsed with PDT-treated Lewis lung carcinoma cells (LLC). This was accompanied by a significant inhibition of tumor growth upon challenge with live LLC cells [40]. In a clinical setting, blood analysis of patients with esophageal squamous cell carcinoma demonstrated that PDT with the PS Photofrin ® abolished the suppressive function of peripheral Treg, but had no effect on Treg numbers [72].…”
Section: Pdt and Adaptive Immunitymentioning
confidence: 99%
“…In turn, NK cell adoptive therapy can improve the tumor-killing effect of PDT. 124 This result is interesting for researchers who are struggling with the numerous side effects of anti-CD47 monoclonal antibody in tumor immunotherapy. 107 Macrophages maintain organic homeostasis by removing abnormal cells and perform important roles in tumorigenesis and progression.…”
Section: Recent Advance Of Nanoparticle-based Pdtmentioning
confidence: 97%
“…A report suggested that PDT targeting of the cellular endoplasmic reticulum can induce endoplasmic reticulum stress via ROS production to suppress "do not eat me" signals (CD47 and Treg cells) while enhancing "eat me" signals (CRT and HSPs) and activate downstream antitumor immune response. 124 This result is interesting for researchers who are struggling with the numerous side effects of anti-CD47 monoclonal antibody in tumor immunotherapy.…”
Section: Recent Advance Of Nanoparticle-based Pdtmentioning
confidence: 97%